Regulação da política pública de saúde suplementar : desafios socioeconômicos das Unimeds - Sociedades Cooperativas de Trabalho Médico - Assumpção, Bruno Gomes de (Universidade do Vale do Rio dos Sinos, 2017)
Brazilian Constitution of 1988 was the first constitutional text to recognize the right to health as a fundamental right, establishing that, besides being the right of everyone and the duty of the State, health care is free to private initiative. The novelty was the adoption of a universal system of access to public health services, intensifying solidarity among legal entities under domestic public law, establishing equality of health care. Supplementary public health policy is an unfolding of health policy, since private institutions may participate in a complementary way to the single health system and according to their latter's guidelines. There is a strong social and economic influence in the regulation of the supplementary public health policy, which is materialized in the obligations imposed on the Health Plan Operators, causing an important socioeconomic discussion about the increase of obligations passed on to the private sector. The State function of protecting public interest before economic strategies of private agents is attributed by the National Agency of Supplementary Health (ANS), based on the conception of a regulatory State and, by mission, the promotion of public interest defense in supplementary health care. The regulatory process is embedded in a scenario of conflicting interests disputes that specify its shape and extension. The articulation between the public and private sectors in health care is a relevant theme for the health system in Brazil, since collective health was constituted fundamentally by analyzing the relations between medicine as a social practice, and the structure of concrete societies in which it grows. Health can not be understood outside its context, since social, economic, political, cultural, behavioral and environmental factors influence both the occurrence of health problems and the design and structure of policy and services offered. The Unimed Cooperative System consists of Brazil's largest healthcare network and the largest cooperative medical work system in the world. There are tensions in the relations between health plan operators, beneficiaries and the National Supplementary Health Agency. There are difficulties in dialogue between the public and private sectors to unfold an efficient supplementary health policy. In the search to provide healthcare services, it is necessary to expand the spaces for dialogue between ANS and health plan operators, in order to improve the understanding of health promotion ideals and possible strategies of practices implementation based on guiding principles that are related to the holistic conception, equity, intersectoriality, social participation and sustainability.
Keywords: Saúde suplementar; Unimed; Política pública; Regulação; Controle social; Supplementary health; Unimed; Public policy; Social control; ACCNPQ::Ciências Humanas::Sociologia